Successful management of a rudimentary uterine horn ectopic pregnancy by combining methotrexate and surgery: A case report - Ângela Rodrigues; Ana Raquel Neves; Maria Geraldina Castro; Miguel Branco; Fernanda Geraldes; Fernanda Águas (Case Reports in Women's Health, 2019)
Pregnancy in a non-communicating rudimentary uterine horn is rare but presents a significantly increased risk of maternal and foetal morbidity due to uterine rupture.We describe a case of rudimentary horn pregnancy diagnosed in the first trimester in an asymptomatic and haemodynamically stable woman. Medical termination of the pregnancy was performed with systemic and intrasacular methotrexate. Laparoscopic uterine horn excision was performed three months after termination.This case shows that early diagnosis of a rudimentary horn pregnancy is key to the successful management of this condition. Preoperative medical termination in an asymptomatic woman proved to be an effective and safe option that minimized surgical risks. Keywords: Mullerian anomaly, Rudimentary horn pregnancy, Ectopic pregnancy, Methotrexate treatment